PERCEPCIÓN ESTUDIANTIL SOBRE EL USO DE ESTRATEGIAS DIDÁCTICAS BASADAS EN EL MODELO PEDAGÓGICO AULA INVERTIDA PARA EL LOGRO DE APRENDIZAJES SIGNIFICATIVOS EN LA ESCUELA DE SECRETARIADO PROFESIONAL DE LA UNIVERSIDAD NACIONAL - Jiménez Vargas, Carlos (2018)
This article shows the perception of the students of the course Procedimientosde Oficina I, group 01-2018, of the Escuela de Secretariado Profesional ofthe UNA, on the use of didactic strategies based on the pedagogical modelflipped classroom for the development of some of the curricular contents. Thealso known as aula invertida incorporates technology as an innovative toolfor significant learning that allows the student to be an active part of theirlearning process, instead of a content recipient. A mixed investigation allowed,through the use of open and closed questions, determine that 92% of studentsagree that significant learning is achieved through the strategies used and alsohighlight the advantages and disadvantages of this model.Keywords: technology, flipped classroom, significant learning, educationalmodel, autonomous learning.